KANDUNGAN SENYAWA KIMIA PADA BUNGA DAN DAUN Chromolaena Odorata (L.) R.M. KING & H. ROBINSON - Yuliasri Jamal; Andria Agusta; Gono Semiadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1996)
An analysis on the chemical compounds of flowers and leaves of Chromolaena Odorata (L.) R.M. King and H. Robinson from Timor island using GCMS, was conducted. Total number of the compound from flowers which can be detected were 18 considered of alkanes, oxygenated hydrocarbon, fatty acid, hydrazine, and alkaloid along with two unidentified compound (1,2). Twenty seven compound detected from leaves were identified as alkanes, fatty acid, alkaloid, hydrazine together with 12 unidentified compound (3-14). Compounds were identified using NIST Library data. Flower and leaves Chromolaena Odorata contained allelopathy compounds such as palmitic aid, linoleic acid, and 2.6-dimetoxy phenol.